The Date and Provenance of the Gospel of Barnabas - Joosten, Jan (The journal of theological studies, 2010)
The so-called Gospel of Barnabas is a curious writing whose historical background remains obscure. The writing is attested in two manuscripts, an Italian one from the sixteenth and a Spanish one from the eighteenth century. Despite recent claims to the contrary, the Italian text can be shown to be the original, from which the Spanish was translated. The date of the Italian text is probably rather earlier than that of the manuscript: strong arguments point to an origin in the fourteenth century. Although it incorporates large amounts of extraneous material, the Gospel of Barnabas does follow the basic narrative thread of the canonical gospels, telling the story of Jesus of Nazareth from his birth to the crucifixion. One of the sources used by the author appears to have been an Italian Diatessaron closely related to the Venetian and Tuscan harmonies edited by Todesco, Vaccari, and Vatasso in 1938, as is shown by a number of unique shared readings.